2016
DOI: 10.1002/jcp.25408
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Conventional Effects of Glucocorticoids in Cancer

Abstract: Synthetic corticosteroids are widely used for the treatment of a variety of diseases, including pre-malignant and malignant conditions. In striking contrast, recent evidence suggests that corticosteroids can bear tumor-promoting effects in solid tumors of epithelial origin. We have recently shown that epithelial tissues, including the mucosa of the oral cavity and the skin, are able to modulate the local concentration of active corticosteroids and to produce steroids de novo. This has important clinical and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 68 publications
0
30
0
Order By: Relevance
“…In the last few years, our focus has been directed on less known secondary effects of GCs, having collected evidence that GCs can influence a variety of functions such as cell migration, differentiation, apoptosis, and proliferation and may have tumor promoting effects, particularly in epithelial neoplasms (Azher et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, our focus has been directed on less known secondary effects of GCs, having collected evidence that GCs can influence a variety of functions such as cell migration, differentiation, apoptosis, and proliferation and may have tumor promoting effects, particularly in epithelial neoplasms (Azher et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic corticosteroids are routinely administered during the treatment of several diseases, including premalignant and malignant conditions, particularly to alleviate side effects of chemotherapy. Recent evidence suggests that corticosteroids may have tumor‐promoting effects, particularly in epithelial neoplasms (Azher et al, ; Herr & Pfitzenmaier, ). In view of the recent discovery of the CAG system, the role of glucocorticoids in the pathobiology of cancer requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In malignant brain tumors, GCs are a first line of care to decrease tumor‐associated brain inflammation and edema . However, the specific effect of GCs on cancer cells from solid tumors is largely disregarded in the clinic and remains only a topic of debate in experimental studies . Psychosocial stress, which increases endogenous GC levels, appears to influence the appearance of malignant brain tumors and correlates with poor prognosis in cancer patients .…”
mentioning
confidence: 99%
“…10 However, the specific effect of GCs on cancer cells from solid tumors is largely disregarded in the clinic and remains only a topic of debate in experimental studies. 11 Psychosocial stress, which increases endogenous GC levels, appears to influence the appearance of malignant brain tumors and correlates with poor prognosis in cancer patients. 12 Moreover, previous studies indicate that GCs can have a profound impact on the gene expression profile of astrocytes and regulate the expression of astrocyte-derived growth factors that are implicated in the proliferation of neural precursor cells.…”
mentioning
confidence: 99%
“…Glucocorticoids are routinely used in the management of blood malignancies but are also employed in the treatment of solid tumours (Haidar & Jeha, 2011). However, it has been suggested that systemic GCs can enhance energy metabolism, which may increase the ability of cancer cells to survive during radiation therapy and chemotherapy in vitro and in vivo (Azher et al, 2016;Seyfried, Shelton, & Mukherjee, 2010;Zhang et al, 2006). In fact, recent evidence shows that adjuvant dexamethasone administration compromises survival of patients with cancer (Pitter et al, 2016;Shields et al, 2015).…”
Section: Potential Role Of Glucocorticoids In the Development And Pmentioning
confidence: 99%